Ephemerality : En uw investering in het hiernamaals ? - Andrin, Muriel; Braeckman, Inge; De Blok, Bart; De Jaeger, Christophe; Dünser, Severin; Eeckhout, Tanguy; Jirkuff, Susi; Kihm, Christophe; Luyckx, Filip; Tribe, Kerry; Exhibition. Ephemerality. Stad Menen. Cultuurcentrum Menen. 2006-11-10. 2006-12-10 (Menen : Cultuurcentrum Menen, 2006)
Aerts, Michaël ; Balleux, Stephan ; Caillat, Sébastien ; Delrue, Ronny ; Deprez, Olivier ; Ervinck, Nick ; Jirkuff, Susi ; Lallemand, Bernard ; Van Lerberghe, Raphaël ; Lybeer, Charlotte ; Raitmayr, Christoph ; Serneels, Stefan ; Tribe, Kerry ; Vosters, Vadim
Ephemerality : En uw investering in het hiernamaals?, diverse locaties in Menen (B), 10 november - 10 december 2006
Engels
Nederlands
boek